The clinical burden of human cystic echinococcosis in Palestine, 2010-2015. - Amer Al-Jawabreh; Suheir Ereqat; Kamal Dumaidi; Abdelmajeed Nasereddin; Hanan Al-Jawabreh; Kifaya Azmi; Nahed Al-Laham; Moath Nairat; Adriano Casulli; Husni Maqboul; Ziad Abdeen (Public Library of Science (PLoS), 2017)
Cystic echinococcosis (CE) is classified by the WHO as a neglected disease inflicting economic losses on the health systems of many countries worldwide. The aim of this case-series study was to investigate the burden of human CE in Palestine during the period between 2010 and 2015.Records of surgically confirmed CE patients from 13 public and private hospitals in the West Bank and Gaza Strip were reviewed. Patients' cysts were collected from surgical wards and formalin-fixed paraffin-embedded (FFPE) blocks were collected from histopathology departments. Molecular identification of CE species /genotypes was conducted by targeting a repeat DNA sequence (EgG1 Hae III) within Echinococcus nuclear genome and a fragment within the mitochondrial cytochrome c oxidase subunit 1, (CO1). Confirmation of CE species/genotypes was carried out using sequencing followed by BLAST analysis and the construction of maximum likelihood consensus dendrogram. CE cases were map-spotted and statistically significant foci identified by spatial analysis. A total of 353 CE patients were identified in 108 localities from the West Bank and Gaza Strip. The average surgical incidence in the West Bank was 2.1 per 100,000. Spot-mapping and purely spatial analysis showed 13 out of 16 Palestinian districts had cases of CE, of which 9 were in the West Bank and 4 in Gaza Strip. Al-Khalil and Bethlehem were statistically significant foci of CE in Palestine with a six-year average incidence of 4.2 and 3.7 per 100,000, respectively.To the best of our knowledge, this is the first confirmation of human CE causative agent in Palestine. This study revealed that E. granulosus sensu stricto (s.s.) was the predominating species responsible for CE in humans with 11 samples identified as G1 genotype and 2 as G3 genotype. This study emphasizes the need for a stringent surveillance system and risk assessment studies in the rural areas of high incidence as a prerequisite for control measures.